ICRISAT and Partners Launch AI-Powered Climate Advisory Initiative to Boost Farmer Resilience - Kumar, Shalander; Subbarao, AVM; Dhulipala, Ram; Kumar; Kishore G.; Santanu Bal; Chandran, Sarath (International Crops Research Institute for the Semi-Arid Tropics, 2025)
The new initiative leverages artificial intelligence (AI) and machine learning (ML) to deliver hyper-local insights for climate-resilient agriculture. Revolutionizing how farmers anticipate and adapt to climate variability, the International Crops Research Institute for the Semi-Arid Tropics (ICRISAT) has joined forces with leading national and international institutions to launch a cutting-edge initiative that harnesses artificial intelligence (AI) and machine learning (ML) to deliver personalized, real-time climate advisory services to farmers.